Training of Higher Educational Institution's Students for Performing Engineering Designs - Nataliia Byshevets (Kherson State University, 2016)
The review of both scientific, methodological and specialized resources on the issue of increasing the level of students' mathematical education at the engineering faculties was made. The experience of implementing information technologies, the Systems of Computer Mathematics in particular, in the process of teaching university students, was studied. Necessity to form mathematical competence of the engineers-to-be by means of information technologies was proved. The technique of instructing students to make engineering designs using information technologies on examples of the subject "Numerical methods" and "Solution of the system of linear equations using Gaussian elimination with selecting the pivot element" was offered. The specific feature of this technique is combination of traditional and innovative educational methods and techniques. We were considering implementation of the methodology offered through the example of the practical lesson on the topic "Solution of nonlinear equation". We first of all offer to consider the Systems of Computer Mathematics as the way to check the results obtained, but after students' gaining corresponding skills, while performing design and graphic works, course and diploma projects, it is worth encouraging them to computerize computational process students several alternative methods of problem solving by means of ICT.